Diagnostic Classification of Autism Spectrum Disorder Using SD Maps of fMRI Data and Machine Learning - Epimack Michael; Sandeep Singh Sengar; Jac Fredo Agastinose Ronickom; Deepesh Kumar (Journal of Medical and Biological Engineering, 2026)

Identification and Characterization of NAC Transcription Factor-Based Simple Sequence Repeat Markers and Genome-Wide Association Studies for Seed Longevity in Alliums - Deepanshu Jayaswal; Deepesh Kumar; Nandita Banerjee; Ankit Badesra; Himanshu Sharma; Garima Yadav; Sanjay Kumar; Rajiv Baliram Kale; Kuldip Jayaswall (Plant Molecular Biology Reporter, 2026)

Extraction of PCR amplifiable DNA from oil, fat and meat samples of reticulated python (Malayopython reticulatus) for genetics and forensics applications - Tannu Balhara; Deepesh Saini; Velmurugan Kodeeswaran; Chinnasamy Ramesh; Sandeep Kumar Gupta (Conservation Genetics Resources, 2026)

Genome-Wide Association and Transcriptome Analysis Unraveling Putative Genes Responsible for High TSS of Allium cepa - Deepanshu Jayaswal; Deepesh Kumar; Vijay Mahajan; Nandita Banerjee; Sonia Sood; Isha Sharma; Sanjay Kumar; Kuldip Jayaswall (Journal of Plant Growth Regulation, 2026)

Whole Genome Sequencing and Subtractive Genomics of Lipaphis erysimi: A Vital Pest of Brassica juncea - Deepanshu Jayaswal; Ratna Prabha; Kuldeep Kumar; Deepesh Kumar; Kuldip Jayaswall; Archana Anokhe; Arvind Nath Singh; Sanjay Kumar; Rekha Kansal (Journal of Plant Growth Regulation, 2026)

Molecular Taxonomy Suggests Presence of Two Distinct Lineages of Blue Sheep (Pseudois nayaur) in Indian Himalayan Region - Deepesh Saini; Gaurav Sonker; Tushar Parab; Vishnupriya Kolipakam; Sambandam Sathyakumar; Salvador Lyngdoh; Sandeep Kumar Gupta (Biochemical Genetics, 2026)

Degraded land: Assessment, impact, restoration, and challenges - Gulshan Kumar Sharma; Dinesh Jinger; I. Rashmi; Manoj Kumar; Nandha Kumar Natrajan; Roomesh Kumar Jena; Raj Kumar; Suresh Kumar; Kavita Kumari; Rajesh Kaushal; Anupam Barh; Trisha Roy; et al. (Journal of Environmental Management, 2026)

Leveraging natural variations in a rice GLTP gene for building climate-smart rice varieties - Bipratip Dutta; Amit Kumar Mazumder; Ritapa Datta; Deepesh Kumar; Archana Singh; Pranab Kumar Mandal; Amolkumar U. Solanke; Amitha Mithra Sevanthi (Plant Physiology Reports, 2025)

Unveiling genetic variation among Bharal (Pseudois nayaur) in the Indian Himalayas using nuclear markers - Deepesh Saini; Gaurav Sonker; Pooja Pant; Vishnupriya Kolipakam; Sambandam Sathyakumar; Salvador Lyngdoh; Sandeep Kumar Gupta (Genetica, 2025)

Unveiling genetic differentiation of Tibetan argali (Ovis ammon hodgsoni) from other subspecies: insights into genetic diversity and phylogenetics of eastern Himalayan population - Deepesh Saini; Himanshi Upadhayay; Tushar Parab; Vishnupriya Kolipakam; Sandeep Kumar Gupta (Mammal Research, 2025)

Immunomodulator and marker-assisted identification of Allium genotypes containing immunological memory against anthracnose - Kuldip Jayaswall; Deepesh Kumar; Deepanshu Jayaswal; R. Sagar; Sanjay Kumar; Ram Kumar Sharma; Kiran Bhagat; Vijay Mahajan; Himanshu Sharma; Surendra Pratap Singh; Isha sharma (Physiological and Molecular Plant Pathology, 2025)

Green initiative: use of cow dung slurry for treatment of industrial effluent - Shivani Thakkar; Megha Deepesh Bhatt; Vishu Patel; Anant Kumar Mishra; Pujan Bhupendra Vaishnav (Environmental Science and Pollution Research, 2025)

Influence of pruning intensity on growth, yield and bio-chemical parameters of guava (Psidium guajava L.) Cv. Shweta under North Indian conditions - Vibhu Pandey; Arvind Kumar; Khushboo Sharma; Deepesh Keshari; Amit Kumar; Devendra Pal (Vegetos, 2025)

Biodegradation efficacy of Exiguobacterium sp. HSK30 towards vegetable packaging LDPE film - Hemlata Sharma; Deepesh Kumar Neelam (Biologia, 2025)

Small RNA sequencing analysis provides novel insights into microRNA-mediated regulation of defense responses in chickpea against Fusarium wilt infection - Parichita Priyadarshini; Gopal Kalwan; Deshika Kohli; Deepesh Kumar; C. Bharadwaj; Kishor Gaikwad; Pradeep Kumar Jain (Planta, 2025)

Allium sativum and Allium cepa offer excellent potential for introgression and production of allicin and high total soluble solids into closely related wild Alliums - Kuldip Jayaswall; Deepesh Kumar; Deepanshu Jayaswal; Himanshu Sharma; Sanjay Kumar; Chibuikem Unamba (South African Journal of Botany, 2025)

Plastic litter: A hidden reservoir for antibiotic-resistant pathogens in coastal ecosystems - Anas Abdulaziz; Nizam Ashraf; Aseera Manika; Mohammed Nowshad Bilutheth; Abdul Riyas Chekkillam; Idrees Babu Konhamkakkada; Kiran Krishna; Reshmi Chandran Rema; Sujith Athiyanathil; Deepesh Velachery; Dinesh Kumar Periyadan Katinhippally (Regional Studies in Marine Science, 2024)

Role of Polymeric Hydrogels in Water Purification: Review - Rajesh Kumar; Shankar Lal Jat; Deepesh Patidar; Prashant Vasistha (Water, Air, & Soil Pollution, 2024)

Correction: Finger millet (Eleusine coracana L.): from staple to superfood—a comprehensive review on nutritional, bioactive, industrial, and climate resilience potential - Simardeep Kaur; Arti Kumari; Karishma Seem; Gurkanwal Kaur; Deepesh Kumar; Surbhi Verma; Naseeb Singh; Amit Kumar; Manish Kumar; Sandeep Jaiswal; Rakesh Bhardwaj; Binay Kumar Singh; et al. (Planta, 2024)

Finger millet (Eleusine coracana L.): from staple to superfood—a comprehensive review on nutritional, bioactive, industrial, and climate resilience potential - Simardeep Kaur; Arti Kumari; Karishma Seem; Gurkanwal Kaur; Deepesh Kumar; Surbhi Verma; Naseeb Singh; Amit Kumar; Manish Kumar; Sandeep Jaiswal; Rakesh Bhardwaj; Binay Kumar Singh; et al. (Planta, 2024)
Main conclusion This review discusses the Finger millet's rich nutritional profile, bioactive potential, and industrial applications, combined with its climate resilience, which make it a promising crop for enhancing food security and promoting sustainable agriculture. This review also highlights its significant potential to address malnutrition and mitigate climate change impacts. Abstract The emergence of Finger millet from “poor man’s staple food” to “a nutrient rich cereal” has encouraged the need to explore this crop at a wider scale. It is a highly significant crop due to its rich nutritional and bioactive profile, diverse biological activities, and promising industrial applications, along with the high climate resilience. This comprehensive review evaluates its nutritional composition by comparing favorably with other cereals and millets and emphasizing its potential to address malnutrition and enhance food security. Furthermore, it explores the phytochemical/bioactive potential and strategies to enhance their bioavailability followed biological activities of Finger millet by highlighting its various health-promoting properties. The review also discusses industrial potential of finger millet including its role in nutraceutical and functional food production, as well as bioenergy generation. In addition, role of Finger millet as a climate-resilient crop; specifically, the available genetic resources and identification of genes and quantitative trait loci (QTLs) associated with major stress tolerance traits have also been discussed. By providing a comprehensive synthesis of existing knowledge, this study offers valuable insights for researchers, policymakers, and stakeholders engaged in efforts to promote sustainable agriculture, enhance food and nutrition security, and mitigate the impacts of climate change.

In Situ Rainwater Conservation Through Half-Moon Terraces for Sustaining C. registanense in the Indian Thar Desert - Suresh Kumar; J. P. Singh; Deepesh Machiwal; R. N. Kulloli; S. K. Barik (Water Conservation Science and Engineering, 2024)

Development of Allium cepa potential intron polymorphism markers for molecular breeding of Alliums - Kuldip Jayaswall; R. Sagar; Deepanshu Jayaswal; Akash Kumar; Surendra Pratap Singh; Romit Seth; Himanshu Sharma; Deepesh Kumar; Vijay Mahajan; Sanjay Kumar; Major Singh (South African Journal of Botany, 2024)

Development of chloroplast derived SSR markers for genus Allium and their characterization in the allies for genetic improvement of Alliums - Kuldip Jayaswall; Himanshu Sharma; Deepanshu Jayaswal; R. Sagar; Abhishek Bhandawat; Akash Kumar; Isha Sharma; Pratibha Chaturvedi; Dalasanuru Chandregowda Manjunathagowda; Deepesh Kumar; Vijay Mahajan; Sanjay Kumar; et al. (South African Journal of Botany, 2023)

Rainfall-runoff modeling using HEC-HMS model in an ungauged Himalayan catchment of Himachal Pradesh, India - C Prakasam; Ravindran Saravanan; Deepesh Machiwal; Mukesh Kumar Sharma (Arabian Journal of Geosciences, 2023)

An overview on endophytic bacterial diversity habitat in vegetables and fruits - Victor Manuel Vásquez Rincón; Deepesh Kumar Neelam (Folia Microbiologica, 2021)

Evaluating homogeneity of monsoon rainfall in Saraswati River basin of Gujarat, India - Deepesh Machiwal; B S Parmar; Sanjay Kumar; Hari Mohan Meena; B S Deora (Journal of Earth System Science, 2021)

Effect of COVID-19 lockdown on noise pollution levels in an Indian city: a case study of Kanpur - Anirudh Mishra; Sanhita Das; Deepesh Singh; Akhilesh Kumar Maurya (Environmental Science and Pollution Research, 2021)

Analysis of trend in temperature and rainfall time series of an Indian arid region: comparative evaluation of salient techniques - Deepesh Machiwal; Ankit Gupta; Madan Kumar Jha; Trupti Kamble (Theoretical and Applied Climatology, 2019)

Evaluating Cost-Effectiveness of Rainwater Harvesting for Irrigation in Arid Climate of Gujarat, India - Deepesh Machiwal; Sanjay Kumar; Devi Dayal (Water Conservation Science and Engineering, 2018)

Spatial modelling of rainfall trends using satellite datasets and geographic information system - Sanjay Kumar; Deepesh Machiwal; Devi Dayal (Hydrological Sciences Journal, 2017)

Effect of compression ratio on performance, emission and combustion characteristics of diesel–acetylene-fuelled single-cylinder stationary CI engine - Anmesh Kumar Srivastava; Shyam Lal Soni; Dilip Sharma; Deepesh Sonar; Narayan Lal Jain (Clean Technologies and Environmental Policy, 2017)

Long-term rainfall trends and change points in hot and cold arid regions of India - Deepesh Machiwal; Devi Dayal; Sanjay Kumar (Hydrological Sciences Journal, 2017)

Evaluating persistence and identifying trends and abrupt changes in monthly and annual rainfalls of a semi-arid region in Western India - Deepesh Machiwal; Madan Kumar Jha (Theoretical and Applied Climatology, 2017)

Identifying abrupt changes and detecting gradual trends of annual rainfall in an Indian arid region under heightened rainfall rise regime - Deepesh Machiwal; Sanjay Kumar; Devi Dayal; Shamsudheen Mangalassery (International Journal of Climatology, 2017)
This study aimed at identification of abrupt change points ( CPs ) and detection of gradual trends in 34‐year (1980–2013) annual rainfall at nine stations of an Indian arid region. The CPs were determined by five tests and their significance was examined by two tests. Furthermore, trends were tested by three tests and their magnitudes were quantified by two tests. Novelty of the study lies in investigating significance of trends sequentially over years by applying Mann–Kendall (M–K) test. The identified CPs were similar for standard normal homogeneity test and cumulative deviations test at most stations. In contrast, Pettitt and Bayesian tests detected CP in years 2002 and 2005 at six and three stations, respectively, and their significance was verified. Results of sequential M–K test did not match with other tests' results. The mean annual rainfall after CP (350–627 mm) increased by 14–80% of the amount before CP (306–444 mm) with 7–42% reduction in coefficient of variation. The box–whisker plots supported these findings. Results of trend tests indicated statistically significant trends at Anjar, Bhachau, Mandvi and Rapar. Trend magnitudes by linear regression prior to CP (−6.2 to 7.1 mm year −1 ) showed an overall increase after CP (4.7–40.8 mm year −1 ) with negative trend at one station. Sen's slope test, showing good harmony with linear regression, revealed that trend magnitudes after CP were 2–10 times higher than that for 34‐year period at six stations. Results of M–K test applied for sequential periods emphasized that rainfall trends are becoming stronger over time. This finding suggests that significance level of increasing rainfall trends may further increase in future. Finally, findings of this study are useful for planners and decision makers for developing policies to meet the challenges of the heightened rainfall in study area. Also, the approach used here may be adopted in other parts of the globe.

Estimating Water Balance of Small Reservoirs in Arid Regions: A Case Study from Kachchh, India - Deepesh Machiwal; Devi Dayal; Sanjay Kumar (Agricultural Research, 2017)

Characterizing rainfall of hot arid region by using time-series modeling and sustainability approaches: a case study from Gujarat, India - Deepesh Machiwal; Sanjay Kumar; Devi Dayal (Theoretical and Applied Climatology, 2016)

Evaluation of oxidant and antioxidant status in living donor renal allograft transplant recipients - Sunil Kumar; Ujjawal Sharma; Ashish Sharma; Deepesh B. Kenwar; Sarbpreet Singh; Rajendra Prasad; Mukut Minz (Molecular and Cellular Biochemistry, 2016)

Role of the cloud adjustment time scale in simulation of the interannual variability of Indian summer monsoon - Deepesh Kumar Jain; Arindam Chakraborty; Ravi S. Nanjundiah (Meteorology and Atmospheric Physics, 2013)

On the role of cloud adjustment time scale in simulating precipitation with Relaxed Arakawa–Schubert convection scheme - Deepesh Kumar Jain; Arindam Chakraborty; Ravi S. Nanjundiah (Meteorology and Atmospheric Physics, 2012)